2023
DOI: 10.1002/mds.29333
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Investigation of Glucose Metabolism in Idiopathic and PRKN‐Related Parkinson's Disease

Abstract: Background Alterations in mitochondrial dysfunction have been implicated in the pathogenesis of Parkinson's disease (PD). Mitochondrial energy production is linked to glucose metabolism, and diabetes is associated with PD. However, studies investigating glucose metabolism in vivo in genetically stratified PD patients and controls have yet to be performed. Objectives The objectives of this study were to explore glucose production, gluconeogenesis, and the contribution of gluconeogenesis to glucose production in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Accumulation of Citric acid, the starting point of the citric acid circle, could also indicate a shift from oxidative phosphorylation to increased glycolysis due to mitochondrial dysfunction, which we previously described. 53,54…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of Citric acid, the starting point of the citric acid circle, could also indicate a shift from oxidative phosphorylation to increased glycolysis due to mitochondrial dysfunction, which we previously described. 53,54…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of Citric acid, the starting point of the citric acid circle, could also indicate a shift from oxidative phosphorylation to increased glycolysis due to mitochondrial dysfunction, which we previously described. 53,54 Mito-PD Only one study investigated the metabolome in PRKN-linked PD 55 and no investigations addressing patients with PINK1-linked PD have been available thus far. We combined these two autosomal recessively inherited forms of PD, as the proteins encoded by these genes act in a common biochemical pathway, mainly involved in the degradation of damaged mitochondria, 6 but also links to alterations of innate immune system have been described to be associated with Parkin and Pink1 dysfunction.…”
Section: Other Metabolitesmentioning
confidence: 99%
“…Energy dysfunction is highly related to the alterations in glucose metabolism in the pathogenesis of PD [115]. Increased levels of glucose [79,71,96] were identified in the blood and CSF of PD patients in three studies, while decreased levels [64,94] were identified in the plasma and CSF of PD patients in two studies.…”
Section: Significant Pathways Of Matched Metabolitesmentioning
confidence: 99%
“…The selective loss of dopaminergic neurons in the substantia nigra and abnormal accumulation of α-synuclein are typical pathological hallmarks of PD [1]. Mitochondrial dysfunction has been identified as an important mechanism in PD and is linked to glucose metabolism [2]. PD patients have alterations in glucose metabolism compared with healthy controls, such as increased glycolysis and gluconeogenesis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction has been identified as an important mechanism in PD and is linked to glucose metabolism [2]. PD patients have alterations in glucose metabolism compared with healthy controls, such as increased glycolysis and gluconeogenesis [2,3]. Furthermore, impaired brain glucose metabolism has been reported in neurodegenerative diseases, including Alzheimer's disease, PD, Huntington's disease, and frontotemporal dementia [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%